Worldviews and values in higher education : institutional governance, leadership, and capacity building - Rao, Madasu Bhaskara; Singh, Abhilasha; Rao, Pulaparthi Mallika (Global perspectives on higher education development, 2025)
Cultural perspectives impact governance, and certain cultures may prefer hierarchical and centralized forms of governance, while others may lean towards more democratic and participatory ones. Governance, guided by ethical worldviews, ensures transparency, accountability, and integrity in decision-making. Worldviews significantly impact leadership styles, and a leader who holds a collectivist perspective would prioritize team building and community outcomes. Leaders' values influence the institution's vision and mission and impact curriculum development, research, and innovation goals. Institutions' approaches to professional development are shaped by their worldviews on continuous learning and improvement. Organizations prioritizing innovation are more likely to allocate greater resources toward advanced training initiatives. Values shape the distribution of resources for capacity building. The chapters presented here link theory, policy, and practice using various research methods. This volume on Worldviews and Values in Higher Education examines the profound influence of worldviews and values in shaping institutional governance, leadership, and capacity building. Integrating worldviews and values into institutional policies ensures that governance, leadership, and capacity building initiatives are coordinated and mutually supportive. Organizations have the ability to evaluate the effectiveness of governance, leadership, and capacity building programs by examining how closely they adhere to the declared values and objectives. This includes the assessment of student achievement, research outcomes, community influence, and the institution's long-term viability. By acknowledging and carefully incorporating worldviews and values, higher education institutions may establish effective, streamlined, equitable, inclusive, and forward-looking settings.